Balancing Individual Political Rights and Institutional Integrity in an Islamic Constitutional Perspective on Party Switching in Indonesia - Andi Sugirman; Irfan Amir; Andri Sutrisno; Agnes Fitryantica; Sholihin Bone (El-Mashlahah, 2025)
The study examined the regulation of party switching among members of Indonesia’s Regional People’s Representative Councils (DPRD) through an integrated analysis of constitutional law, political rights theory, and Indonesian Islamic jurisprudence. It critically evaluated Constitutional Court Decision No. 88/PUU-XXI/2023 to assess how individual political rights are balanced with institutional stability. Employing a normative legal research approach, the study combined statutory, case-based, and conceptual analyses, enriched with comparative insights from Malaysia, Pakistan, India, and South Africa. The findings found out that current legal mechanisms, particularly the Inter-Temporal Replacement (PAW) procedure under Article 193 of Law No. 23 of 2014, disproportionately empower political parties, undermining electoral legitimacy and legislators’ autonomy. By integrating maqāṣid al-sharī‘ah principles, including al-‘adl (justice), al-maṣlaḥah (public welfare), amanah (trust), and ḥurriyyah siyāsiyyah (political freedom), the study proposed normative and practical reforms to enhance proportionality, transparency, and fairness in regulating party switching. The research contributed to scholarship by linking constitutional law, political representation, and Islamic ethical principles, providing theoretical insights and actionable recommendations to strengthen democratic representation, protect political rights, and reinforce institutional legitimacy in Indonesia.